Analisis Kualitatif Miskonsepsi Siswa pada Materi Transformasi Geometri menggunakan Media Komik Interaktif Berbasis HTML sebagai Alat Diagnosis - Aghna Ikhtiara Hendra R; Nuryami (PT Cendekia Education Center, 2026)
This study aims to qualitatively analyze the misconceptions of 10th-grade students in distinguishing between translation, rotation, reflection, and dilation using an HTML-based interactive comic as a diagnostic tool, rather than merely as a learning medium. The study employed a phenomenological case study design involving 30 students from SMAIT Kyai Sekar Al-Amri who took a comic-based pretest-posttest; subsequently, 6 students representing high, moderate, and low performance categories were selected for interviews and questionnaires. Data were triangulated through qualitative content analysis. The results showed an increase in the average class score from 44.0 to 72.7. A tiered pattern of misconceptions was identified: low-ability students exhibited fundamental conceptual misconceptions, moderate-ability students exhibited procedural misconceptions, while high-ability students only made minor errors due to overconfidence. Interactive comics proved effective in revealing patterns of misconceptions in a more authentic and emotionally comfortable manner; therefore, they are recommended as an alternative diagnostic tool with different remediation strategies for each student ability category.